Weight Gain and Haematolgical Profile of Broiler Chicks Fed a Maize-Soyabean Diet Supplemented with Different Levels of Methionine, Sodium Sulphate and Sodium Sulphite - Akpet, S.O.; Essien, A.; Orok, E.E.; Etop, S.C.; Ukorebi, B.A. (International Journal of Poultry Science, 2009)
An experiment was carried out to investigate the effect of substituting synthetic methionine with sodium sulphate and sodium sulphite in maize-soyabean diets fed to broiler chicks on weight and haematological profile. Two hundred and forty (240) unsexed Hubbard day old broiler chicks were fed iso-caloric and iso-nitrogenous maize-soyabean diets (3,000 cal/kg and 22% crude protein) for four weeks. There were eight treatment groups, T1-T8, each replicated three times. T1 had no methionine, T2 had 3% methionine, T3 had 3% sodium sulphate, T4 had 3% sodium sulphite, T5 had 1.5% methionine and 1.5% sodium sulphate, T6 had 1.5% methionine and 1.5% sodium sulphate T7 had 1.5% methionine and 1.5% sodium sulphite while T8 had 1.5% methionine and 1% sodium sulphite. Chicks in T6 had the highest average weekly weight gain of 106.58 g while birds in T8 had the lowest average weekly weight gain (79.94 g). The average weekly weight gain of birds in T1, T2 and T5 did not differ significantly (p>0.05) from one another. Likewise the average weekly weight gain of birds in T1, T2, T3 T4 and T5 did not differ significantly (p>0.05) from one another. The average weekly weight gain of chicks in T7 and T8 which had the lowest weight gains, also did not differ significantly (p>0.05). All haematological parameters evaluated fell within safe precincts as stipulated in literature. Treatment 6 is therefore recommended for broiler starter rations alongside T2 and T5 because they did not differ significantly (p>0.05) from one another.